SNP discovery in black cottonwood (Populus trichocarpa) by population transcriptome resequencing - GERALDES, ARMANDO; PANG, JOHNSON; THIESSEN, NINA; CEZARD, TIMOTHEE; MOORE, RICHARD; ZHAO, YONGJUN; TAM, ANGELA; WANG, SHUCAI; FRIEDMANN, MICHAEL; BIROL, INANC; JONES, STEVEN J.M; CRONK, QUENTIN C.B; et al. (Molecular ecology resources, 2011)
The western black cottonwood (Populus trichocarpa) was the first tree to have its genome fully sequenced and has emerged as the model species for the study of secondary growth and wood formation. It is also a good candidate species for the production of lignocellulosic biofuels. Here, we present and make available to the research community the results of the sequencing of the transcriptome of developing xylem in 20 accessions with high-throughput next generation sequencing technology. We found over 0.5 million putative single nucleotide polymorphisms (SNPs) in 26 595 genes that are expressed in developing secondary xylem. More than two-thirds of all SNPs were found in annotated exons, with 18% and 14% in regions of the genome annotated as introns and intergenic, respectively, where only 3% and 4% of sequence reads mapped. This suggests that the current annotation of the poplar genome is remarkably incomplete and that there are many transcripts and novel genes waiting to be annotated. We hope that this resource will stimulate further research in expression profiling, detection of alternative splicing and adaptive evolution in poplar.